2016
DOI: 10.1021/jacs.6b05281
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Engineering of Potent Sensitizers for Very Efficient Light Harvesting in Thin-Film Solid-State Dye-Sensitized Solar Cells

Abstract: Dye-sensitized solar cells (DSSCs) have shown significant potential for indoor and building-integrated photovoltaic applications. Herein we present three new D-A-π-A organic sensitizers, XY1, XY2, and XY3, that exhibit high molar extinction coefficients and a broad absorption range. Molecular modifications of these dyes, featuring a benzothiadiazole (BTZ) auxiliary acceptor, were achieved by introducing a thiophene heterocycle as well as by shifting the position of BTZ on the conjugated bridge. The ensuing hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
104
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 27 publications
8
104
1
Order By: Relevance
“…1a) brings out the outstanding attributes of both dyes. The recently introduced XY1 sensitizer, a D-A-π-A dye, has a very high molar extinction coefficient and spectral response that extends beyond 700 nm, whereas D35 is an organic D-π-A dye endowed with a judiciously designed arylamine donor structure, which suppresses electron recapture by the Cu(II) complex from the TiO 2 conduction band and generates a high open-circuit potential 30,32 . Even during the early stage of this study we found that the XY1 dye in combination with D35 showed impressive photovoltaic metrics, specifically under indoor and ambient light illumination.…”
Section: Resultsmentioning
confidence: 99%
“…1a) brings out the outstanding attributes of both dyes. The recently introduced XY1 sensitizer, a D-A-π-A dye, has a very high molar extinction coefficient and spectral response that extends beyond 700 nm, whereas D35 is an organic D-π-A dye endowed with a judiciously designed arylamine donor structure, which suppresses electron recapture by the Cu(II) complex from the TiO 2 conduction band and generates a high open-circuit potential 30,32 . Even during the early stage of this study we found that the XY1 dye in combination with D35 showed impressive photovoltaic metrics, specifically under indoor and ambient light illumination.…”
Section: Resultsmentioning
confidence: 99%
“…A common strategy for reducing aggregation for both metal‐complex dyes and organic sensitizers is the use of alkyl or alkoxy chains, present in just about all of the highest‐performing sensitizers . One of the more exciting examples of a novel antiaggregation unit was the use of a glucose derivative attached by click chemistry to a dianchoring phenothiazine sensitizer, reported by Manfredi et al.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38][39] In a general manner, this last strategy offers great advantages: owing to the reduced number of reactants, the workup is simplified and the production cost is even reduced. As molecule 1 is not yet commercially available but is a unique building block for creating symmetrical or unsymmetrical π-conjugated D-A molecules, [42][43][44][45][46][47][48] the suggestion of an effective and simple synthetic protocol should be of interest to many chemists. In this spirit, we recently synthesized benzothiadiazole (Bz)-based symmetrical molecules by using dibromobenzothiadiazole (diBrBz) and 2thiophenecarbaldehyde (ThCHO) as starting materials (Scheme 1, top) through phosphine-and additive-free direct C-H arylation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it may be considered environmentally and economically attractive as well as efficient. So far, there have been only a few reports on the synthesis of 1 in good yields (i.e., more than 40 %), and the related synthetic protocols were based on Suzuki [43][44][45][46][47] or Stille [48] coupling reactions (see (thiophen-2-yl)benzo [1,2,5]thiadiazole (54 % intermediate yield), which was then formylated through a classical route to afford 1. [40] In the present study, we investigated the disymmetrization of the Bz unit through the synthesis of the mono-adduct 5-(7bromo-2,1,3-benzothiadiazol-4-yl)-2-thiophenecarbaldehyde (1, Scheme 1).…”
Section: Introductionmentioning
confidence: 99%